Pengaruh penggunaan media visual animasi terhadap hasil belajar peserta didik pada pembelajaran matematika - Aji Aprian Suganda; Arjudin; Junaidi; Sripatmi (Mandalika Mathematics and Educations Journal, 2024)
This research aims to know the influence of using visual animation media on students' learning outcomes in mathematics education. The research design employed is quantitative research with an experimental method. The design used in this study is quasi-experimental design. Data collection techniques include tests and observations. The test instrument consists of 5 essay questions used to assess students' learning outcomes and observation guidelines are used to gather desired data based on the research objectives. The population of this study is all eighth-grade students, totaling 196 students. The sampling technique used in this study is cluster random sampling. Class VIII-A with 29 students is the sample group that uses animation media in their learning (experimental class), while Class VIII-B with 28 students is the sample group that learns without animation media (control class). The data analysis techniques used include normality and homogeneity tests as prerequisites, and the t-test as the hypothesis test. Based on the hypothesis test results using the t-test at a significance level of 5%, the obtained value of t-value is 2,068 and t-table is 2,004. Since the value of tvalue > ttable, so the null hypothesis H0 is rejected, indicating that there is an influence in the use of visual animation media as a mathematics learning media on students' learning outcomes.